Perceived Covid-19-crisis intensity and family supportive organizational perceptions as antecedents of parental burnout: A study conducted in Italy in March/April 2021 and 2022 - Redaelli, Marta; van Engen, Marloes L.; André, Stéfanie (Frontiers in Psychology, 2022)
The purpose of this study is to investigate to what extent perceived Covid-19-crisis intensity (PCCI) leads to the experience of parental burnout (PB), a syndrome characterized by exhaustion, emotional detachment from one’s own children and a sense of inefficacy in the role as parent. Furthermore, the mediating role of work–family conflict (WFC) is examined. The buffering effect of family supportive organizational perceptions during the pandemic (FSOP-p) on the relationship between work–family conflict and parental burnout is also explored. Data were collected in March–April 2021 and March/April 2022. In spring 2021, 222 Italian working parents with at least one minor child living at home filled out the questionnaire. Data from 2021 showed that PCCI was positively related to the experience of parental burnout. Moreover, WFC mediated this relationship. No significant interaction effect was found for FSOP-p; however it was found that FSOP-p is negatively related to PCCI and WFC, and indirectly to parental burnout. In spring 2022, we examined whether there were changes in PCCI, WFC, and FSOP-p in a sample of 83 Italian parents. Moreover, for the second data collection we examine the tensions experienced by parents in their families about vaccination and infection precaution measures (e.g., Covid-19 vaccination passport). The results are different in 2022; the effect of PCCI on parental burnout is now completely mediated by the amount of WFC. It seems that now we go ‘back to normal’ and homeworking has become more optional for many, there is still an effect of PCCI on WFC, but no longer directly on parental burnout. Furthermore, the prevalence of PCCI in 2022 is lower than in 2021, while WFC and FSOP-p are not significantly different between the two timepoints. As family supportive organizational perceptions reduce the level of perceived Covid-19 intensity, organizations are urged to develop practices of support and to create a supportive environment.